Potential clusters for joint grazing land in Kiteto District, Manyara region - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing potential clusters of villages for joint village land use planning as defined by the Sustainable Rangeland Management project Kiteto District, Manyara region, Tanzania, implemented by the International Livestock Research Institute and partners.